Porosity film, separator for secondary battery, and secondary battery
By using organic resins of fluoride and propionate monomers in lithium-ion battery separators and combining inorganic particles such as aluminum silicate, the adhesion and thermal dimension stability of the separator and electrodes are solved, and efficient and low-cost battery production and performance improvements are achieved.
Patent Information
- Application Number
- JP2023159396
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art has challenges in improving the adhesion and thermal dimensional stability of the lithium-ion battery separator and electrode, and is costly, affecting the production efficiency and performance of the battery.
An organic resin containing fluoride and propionate monomer is used to combine inorganic particles such as aluminum silicate to adjust the surface elastic modulus and surface roughness to form a separator material with excellent adhesion and thermal dimension stability.
It realizes good adhesion and thermal dimensional stability between the lithium-ion battery separator and electrode, reduces the internal resistance of the battery, improves the production efficiency and performance of the battery, and controls costs.
Smart Images

Figure 2025050544000001 
Figure 2025050544000002 
Figure 2025050544000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous film, a separator for a secondary battery, and a secondary battery. [Background technology]
[0002] 2. Description of the Related Art Secondary batteries such as lithium-ion batteries are widely used in automobile applications such as electric vehicles, hybrid vehicles, and plug-in hybrid vehicles; in portable digital devices such as smartphones, tablets, mobile phones, laptops, digital cameras, digital video cameras, and portable game consoles; power tools, electric motorcycles, and electrically assisted bicycles.
[0003] In particular, lithium-ion batteries are considered to be suitable for electric vehicles due to their high energy density and durability against repeated charging and discharging, and there is a trend toward ever-increasing capacities, so ensuring safety is important.
[0004] A lithium ion battery generally has a configuration in which a positive electrode in which a positive electrode active material is laminated on a positive electrode current collector, a negative electrode in which a negative electrode active material is laminated on a negative electrode current collector, and a secondary battery separator and an electrolyte are interposed between them.
[0005] Polyolefin-based porous substrates are used as separators for secondary batteries. The characteristics required for separators for secondary batteries include a characteristic of containing an electrolyte in the porous structure to enable ion migration, a shutdown characteristic of stopping discharge by melting the porous structure with heat and stopping ion migration when the lithium-ion battery generates abnormal heat, and suppression of thermal contraction.
[0006] Lithium ion batteries are also required to have excellent battery characteristics such as high output and long life, and are required to exhibit and maintain good battery characteristics without reducing the high output characteristics.
[0007] Furthermore, in order to improve the energy density of lithium-ion batteries, the battery configuration is being replaced from a wound type to a stacked type. In the case of a stacked type, in the manufacturing process of a secondary battery using an electrode stack in which a positive electrode, a separator, and a negative electrode are stacked, the stack structure is displaced when the electrode stack is transported, which causes a problem of deterioration in the yield of battery production. In addition, after the electrolyte is injected into the battery, the stack structure is displaced due to the expansion and contraction of the electrodes during the initial charge and discharge process, forming gaps, which causes a decrease in capacity during the initial charge and discharge, and also reduces the yield.
[0008] In order to solve the above problems, in Patent Document 1, a heat-resistant layer containing inorganic particles is formed on at least one surface of a porous substrate, which is a substrate for a separator for a secondary battery, to suppress thermal shrinkage in order to improve safety. In Patent Document 2, an adhesive layer formed on a heat-resistant layer is laminated to improve transportability by developing adhesiveness (dry adhesiveness) between the separator and the electrode before the electrolyte is impregnated. In Patent Document 3, a porous layer mainly composed of a polyvinylidene fluoride resin that has adhesiveness (wet adhesiveness) with the electrode in a state impregnated with the electrolyte is laminated on a porous substrate made of polyolefin, making it difficult for gaps to occur between the electrode and the separator during charging and discharging.
[0009] Furthermore, Patent Documents 4 and 5 discuss improving the yield during battery production and the yield during initial discharge by exhibiting both dry and wet adhesive properties. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2013-080676 A [Patent Document 2] Japanese Patent No. 6191597 [Patent Document 3] JP 2012-221741 A [Patent Document 4] International Publication No. 2013 / 151144 [Patent Document 5] International Publication No. 2016 / 098684 Summary of the Invention [Problem to be solved by the invention]
[0011] However, in Patent Document 1, α-alumina is mainly used as the inorganic particles contained in the layer as heat-resistant particles, and the high Vickers hardness of alumina may cause the device to be scraped during the formation of the heat-resistant layer, resulting in severe wear and tear, which may lead to high costs. In Patent Document 2, when the electrolyte is impregnated after the dry adhesion is expressed, the acrylic resin may swell or dissolve in the electrolyte, and the separator may easily peel off from the electrode. In that case, even if the separator and the electrode are dry-bonded, a gap is formed between the separator and the electrode when the separator is actually immersed in the electrolyte in the battery, so the distance between the electrodes is not constant during initial charge and discharge, causing a decrease in capacity during initial discharge, and not leading to an improvement in yield. In Patent Document 3, there is no mention of dry adhesion, so that the electrode and the separator are misaligned during battery production, and the yield is also not improved.
[0012] In addition, in the methods described in Patent Documents 4 and 5, if the dry adhesion and wet adhesion are strong, the electrolyte is difficult to penetrate into the electrodes and separator when the electrolyte is injected, which may result in a decrease in battery characteristics such as rate characteristics and life characteristics. On the other hand, if both the dry adhesion and wet adhesion are weak, it is difficult to improve the yield during battery production and initial charge and discharge.
[0013] As mentioned above, the adhesiveness between the electrode and the porous film is required by the hot pressing process in the manufacturing process of the secondary battery. In order to improve the adhesiveness with the electrode, it has been considered to increase the organic resin particles that are responsible for the adhesion with the electrode, but there is a problem that the rate characteristic and the battery life are deteriorated due to the increase in the battery resistance. Furthermore, it is necessary to achieve both the heat-resistant layer and the adhesiveness at low cost.
[0014] In view of the above problems, an object of the present invention is to provide a porous film having excellent adhesion to electrodes, thermal dimensional stability, and low resistance at low cost. [Means for solving the problem]
[0015] Therefore, the inventors have discovered that a porous film having excellent adhesion to electrodes, thermal dimensional stability, and low resistance can be produced at low cost by distributing the organic particles in the surface layer and separating them from the inorganic particles, the porous film having a porous layer containing inorganic particles that improve abrasion resistance, the organic resin containing fluorine and having structural units derived from acrylic ester monomers, and the maximum value of the surface elastic modulus when the surface elastic modulus of the porous layer is measured 50 times is defined as α, and the maximum value α and the arithmetic mean height (Sa) of the porous layer in a 2200 μm square are within a predetermined range.
[0016] In order to solve the above problems, the porous film of the present invention has the following configuration. (1) A porous film comprising a porous substrate and a porous layer containing inorganic particles and an organic resin on at least one surface of the porous substrate, the organic resin containing fluorine and having a structural unit derived from an acrylic acid ester monomer, the surface elastic modulus of the porous layer being measured 50 times, and the maximum value of the surface elastic modulus being α, wherein α is 1 GPa or more and 10 GPa or less, and the arithmetic mean height (Sa) of the porous layer in a 2200 μm square is 10 nm or more and 90 nm or less. (2) The porous film according to (1), wherein the mass content of the inorganic particles contained in the porous layer is 50% by mass or more and 95% by mass or less with respect to the mass of the entire porous layer. (3) The porous film according to (1) or (2), in which, when the total volume of all components of the porous layer is taken as 100 volume %, the volume content γ of inorganic particles and the occupancy rate δ of inorganic particles in the surface portion of the porous layer satisfy 0<δ / γ<1. (4) The porous film according to any one of (1) to (3), wherein the surface elastic modulus of the porous layer is measured 50 times, and the minimum value of the surface elastic modulus is defined as β, and the value of α / β is 1.5 or more and less than 10. (5) The porous film according to any one of (1) to (4), wherein the organic resin contains organic resin particles. (6) The porous film according to any one of (1) to (5), wherein the type of the inorganic particles is at least one particle selected from the group consisting of boehmite, barium sulfate, and magnesium oxide. (7) The porous film according to any one of (1) to (6), wherein the inorganic particles have an average particle size of 0.3 μm or more and 1.2 μm or less. (8) The porous film according to any one of (1) to (7), wherein the organic resin has a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer and a structural unit derived from a (meth)acrylic acid ester monomer having two or more reactive groups per molecule. (9) The porous film according to (8), wherein the (meth)acrylic acid ester monomer having two or more reactive groups per molecule contains an alkyldiol group having six or more carbon atoms. (10) The porous film according to (8), wherein the organic resin further has at least one structural unit derived from a (meth)acrylic acid ester monomer containing a cyclic hydrocarbon group. (11) The porous film according to (8), wherein the organic resin contains structural units derived from (meth)acrylic acid ester monomers having two or more reactive groups per molecule in an amount of 0.5% by mass or more and less than 10.0% by mass, when the total monomer components constituting the organic resin are taken as 100% by mass. (12) The porous film according to (10), wherein the organic resin contains at least one structural unit derived from a (meth)acrylic acid ester monomer having a cyclic hydrocarbon group in an amount of 20% by mass or more and 70% by mass or less, when the total monomer components constituting the organic resin are taken as 100% by mass. (13) The porous film according to (8), wherein the organic resin contains a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer in an amount of more than 20% by mass and not more than 60% by mass, when the total monomer components constituting the organic resin are taken as 100% by mass. (14) A separator for a secondary battery, comprising the porous film according to any one of (1) to (13). (15) A secondary battery comprising the separator for a secondary battery according to (14). (16) A vehicle, an unmanned transport vehicle, an electronic device, or a power storage device including the secondary battery according to (15). Effect of the Invention
[0017] According to the present invention, a porous film having excellent adhesion to an electrode, thermal dimensional stability, and low resistance can be provided at low cost. In addition, by using the porous film as a battery separator, a secondary battery having improved yield in the battery production process, excellent battery life, and high-rate characteristics can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The porous film of the present invention comprises a porous substrate and a porous layer containing inorganic particles and an organic resin on at least one surface of the porous substrate, the organic resin containing fluorine and having a structural unit derived from an acrylic acid ester monomer, and further characterized in that, when the maximum value of the surface elastic modulus of the porous layer when the surface elastic modulus is measured 50 times is taken as α, α is 1 GPa or more and 10 GPa or less, and the arithmetic mean height (Sa) of the porous layer in a 2200 μm square is 10 nm or more and 90 nm or less.
[0019] The porous film of the present invention will be described in detail below.
[0020] In the porous film of the present invention, the organic resin contains fluorine and has a structural unit derived from an acrylic acid ester monomer, which reduces the surface free energy of the organic resin, so that the organic resin can be unevenly distributed on the surface side of the film in the porous layer containing inorganic particles and the organic resin, thereby improving the dry adhesion and wet adhesion of the porous layer to the electrode.
[0021] In addition, in the porous film of the present invention, when the maximum value of the surface elastic modulus of the porous layer when the surface elastic modulus is measured 50 times is defined as α, α is 1 GPa or more and 10 GPa or less. The porous layer of the present invention contains inorganic particles and organic particles, and there are parts where inorganic particles are present and parts where organic particles are present on the surface of the porous layer. In general, the surface elastic modulus of inorganic particles is higher than that of organic resins. Therefore, in measuring the surface elastic modulus of the porous layer, when the parts where inorganic particles are present on the surface of the porous layer are measured, the value is higher than when the parts where organic particles are present on the surface of the porous layer are measured. Even if the organic resin has a structure in which the organic resin is unevenly distributed on the surface side as described above, by measuring the surface elastic modulus many times, such as 50 times, α can indicate the surface elastic modulus of inorganic particles. When α is less than 1 GPa, the strength of the porous film is reduced, and when the porous film is used in a secondary battery as a separator for the secondary battery, the short circuit resistance (nail penetration resistance) is significantly reduced. On the other hand, when α exceeds 10 GPa, the wear of parts during the dispersion process of organic resin and inorganic particles and the wear of parts during the coating process of the porous layer are significantly reduced, leading to high costs. α is preferably 1 GPa or more and 10 GPa or less, more preferably 3 GPa or more and 9 GPa or less, and even more preferably 5 GPa or more and 8 GPa or less. In order to form a porous layer with α within the above range, the selection of inorganic particles is important, as will be described in detail later.
[0022] Furthermore, the porous film of the present invention has an arithmetic mean height (Sa) of the porous layer in a 2200 μm square of 10 nm or more and 90 nm or less. By setting the arithmetic mean height (Sa) of the porous layer in a 2200 μm square in the above range, a uniform membrane is provided, and a large amount of lithium ions can uniformly pass through, so that the high-rate characteristics are improved when the porous film is used as a secondary battery separator in a secondary battery. In addition, in the adhesion process (heat press) between the porous film and the electrode, heat is uniformly transferred, and the adhesion to the electrode is improved. The arithmetic mean height (Sa) of the porous layer in a 2200 μm square is preferably in a range of 10 nm or more and 90 nm or less, more preferably 30 nm or more and 80 nm or less, and even more preferably 50 nm or more and 70 nm or less. When the arithmetic mean height (Sa) of the porous layer in a 2200 μm square is less than 10 nm, the porous layer becomes too dense, hindering the permeation of lithium ions, and the high-rate characteristics are reduced. On the other hand, if the arithmetic mean height (Sa) of the porous layer in a 2200 μm square exceeds 90 nm, the resistance uniformity within the surface of the porous layer decreases and differences in the mobility of lithium ions occur, resulting in a decrease in the high-rate characteristics. Here, the arithmetic mean height (Sa) can be adjusted to a predetermined range by adjusting the conditions of the average particle size and shape of the inorganic particles and the average particle size and shape of the organic resin.
[0023] [Porous layer] The porous layer in the present invention refers to a layer that contains inorganic particles and organic resin, has micropores inside, is electrically insulating, and is also permeable to ions such as lithium ions. The porous layer preferably satisfies the following relationship: 0<δ / γ<1, where γ (%) is the volume content of inorganic particles when the total components of the porous layer are 100% by volume, and δ (%) is the occupancy rate of inorganic particles on the surface of the porous layer. When δ / γ is smaller than 1, it indicates that the occupancy rate of inorganic particles on the surface of the porous layer is lower than the mass content of inorganic particles in the entire porous layer, that is, it indicates that the organic resin is unevenly distributed on the surface of the porous layer. By unevenly distributing the organic resin on the surface of the porous layer, the surface has a large amount of organic resin, and therefore exhibits sufficient dry adhesion and wet adhesion with the electrode. When δ / γ=0, it indicates that the occupancy rate of inorganic particles on the surface of the porous layer is 0%, and only organic resin is distributed on the surface. In that case, blocking between the porous films occurs, and peeling of the porous layer may occur when the porous film is used, so δ / γ is preferably greater than 0. The ratio δ / γ is preferably less than 1, more preferably 0.5 or less, and further preferably 0.3 or less. The lower limit of δ / γ is not particularly limited, but it is preferable that it is 0.01 or more.
[0024] The method for forming a porous layer having a δ / γ ratio within the above range is not particularly limited. The porous layer may be formed through a two-stage coating process using two types of coating liquids, or may be formed through a one-stage coating process using one type of coating liquid. However, if the porous layer can be formed through a one-stage coating process, the number of coatings can be reduced, which reduces costs, so it is more preferable to form the porous layer through a one-stage coating process using one type of coating liquid. To achieve a one-stage coating process, for example, the surface free energy of the organic resin, the viscosity of the coating liquid, the solid content concentration, and the drying temperature can be appropriately adjusted to make δ / γ within a predetermined range. The solid content concentration of the coating liquid is preferably 5% by mass or more and 40% by mass or less. For example, by setting the solid content concentration of the coating liquid within the above range, coating stability and surface uneven distribution of the organic resin during coating and drying can be achieved at the same time, so that the value of δ becomes smaller, and δ / γ tends to become smaller. In addition, the solution viscosity of the coating liquid is preferably 5 mPa·s or more and 50 mPa·s or less. By setting the solution viscosity of the coating liquid within the above-mentioned range, the dispersibility of the coating liquid and the surface uneven distribution of the organic resin during coating and drying can be achieved at the same time, so the value of δ becomes smaller, and δ / γ tends to become smaller. In addition, the drying temperature is preferably 40°C or higher and 100°C or lower. By setting the drying temperature within the above-mentioned range, the surface uneven distribution of the organic resin due to layer separation during drying is likely to occur, and the value of δ becomes smaller, so δ / γ tends to become smaller. If the drying temperature is less than 40°C, the solvent of the coating liquid takes a long time to dry, which increases costs. On the other hand, if the drying temperature is higher than 100°C, when organic resin particles are used as the organic resin, the amount of heat during drying increases, and the particle shape cannot be maintained, forming a film, so that the surface uneven distribution of the organic resin particles does not occur, and δ / γ=1. Therefore, by setting it within a specified range, δ / γ can be adjusted to a specified range, and good dry adhesion and wet adhesion to the electrode and low costs due to improved coating and drying speed can be achieved at the same time.
[0025] The volume content γ of the inorganic particles is preferably 30% by volume or more and 90% by volume or less, more preferably 40% by volume or more and 75% by volume or less, and even more preferably 50% by volume or more and 60% by volume or less, when the total components of the porous layer are taken as 100% by volume. By making the volume content β of the inorganic particles 30% by volume or more, sufficient thermal dimensional stability can be obtained. Furthermore, by making it 80% by volume or less, the content of the organic resin particles becomes sufficient, and the dry adhesion and wet adhesion to the electrode are improved. The volume content α of the inorganic particles relative to the entire porous layer can be calculated by the measurement method described in the examples.
[0026] The occupancy rate δ of the inorganic particles in the surface portion of the porous layer is preferably greater than 0%. More preferably, it is 1% or more, and even more preferably, it is 5% or more. When δ is greater than 0%, the number of coatings can be reduced by a single-stage coating process, or the cost of coating materials can be reduced by reducing the amount of raw materials. The upper limit is not particularly limited, but it is preferably less than 50%. More preferably, it is 30% or less, and even more preferably, it is 20% or less. When it is less than 50%, the dry adhesion and wet adhesion to the electrode are good. The occupancy rate δ of the inorganic particles in the surface portion of the porous layer can be calculated by the measurement method described in the examples. The surface portion of the porous layer is the surface layer at a depth that affects the outer surface of the porous layer and the adhesion to the electrode, and is shown by an image obtained using SEM-EDX described later.
[0027] The surface free energy of the porous layer is preferably 10 mN / m or more and 80 mN / m or less, more preferably 15 mN / m or more and 70 mN / m or less, and even more preferably 20 mN / m or more and 60 mN / m or less. By making it 10 mN / m or more, the coating stability of the porous layer is improved. Also, by making it 80 mN / m or less, surface uneven distribution due to layer separation of the organic resin is likely to occur, and it is easy to control δ / γ.
[0028] The porous layer preferably has a glass transition temperature of 20°C or more and less than 90°C. The lower limit is more preferably 30°C or more, and more preferably 40°C or more. The upper limit is more preferably 70°C or less, and more preferably 60°C or less. By setting the glass transition temperature at 20°C or more, swelling in the electrolyte is suppressed, and the rate characteristics and life characteristics are improved. By setting the glass transition temperature at less than 90°C, both adhesion to the electrode and blocking resistance between the porous films can be achieved. In order to set the glass transition temperature in an appropriate range, a specific monomer group can be appropriately selected. Here, the glass transition temperature in this specification refers to the midpoint glass transition temperature measured by differential scanning calorimetry (DSC) according to JIS K7121:2012. The midpoint glass transition temperature is the temperature at the point where a straight line equidistant in the vertical axis direction from the straight line extended from each baseline intersects with a curve of a stepwise change part of the glass transition.
[0029] The porous layer preferably has an α / β value calculated from the relationship between the maximum difference α and the minimum value β, where β is the minimum value of the surface elastic modulus of the porous layer measured 50 times. The lower limit is more preferably 2.0 or more, and even more preferably 3.0 or more. The upper limit is more preferably 6.0 or less, and even more preferably 5.0 or less. By making the α / β value 1.5 or more, the dry adhesion and wet adhesion to the electrode are improved. Furthermore, by making the α / β value less than 10, the elastic modulus distribution on the surface of the porous layer becomes uniform, and the ion conductivity becomes uniform even after adhesion to the electrode, resulting in good battery characteristics.
[0030] (1) Organic resin The organic resin in the present invention preferably has adhesiveness to the electrode. By distributing the organic resin having adhesiveness to the electrode unevenly on the surface layer of the porous film, the ion permeability is improved, and the rate characteristic is improved. In addition, by lowering the surface free energy of the organic resin, the δ / γ can be lowered.
[0031] The organic resin preferably contains fluorine and has a structural unit derived from an acrylic acid ester monomer. In particular, the organic resin preferably has a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer. The organic resin having a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer can be a mixture containing a polymer made of a fluorine-containing (meth)acrylic acid ester monomer, or a copolymer containing a polymer polymerized using a fluorine-containing (meth)acrylic acid ester monomer. This allows the organic resin to be unevenly distributed on the surface side by lowering the surface free energy of the organic resin, thereby improving the adhesion of the porous layer to the electrode. In this specification, the "structural unit derived from an acrylic acid ester monomer" is represented by the following general formula (1).
[0032] [ka]
[0033] (In formula (1), R 1 is hydrogen or a methyl group, R 2 represents a hydrocarbon group having 1 to 10 carbon atoms, and a represents the degree of polymerization. In formula (1), R 1 are each independently a hydrogen or a methyl group. 1 The monomer with hydrogen is acrylate, R 1 However, the monomer with a methyl group represents a methacrylate.
[0034] R 2 is a hydrocarbon group having 1 to 10 carbon atoms. The hydrocarbon group may have an unsaturated bond, and may be either a straight-chain hydrocarbon group or a branched-chain hydrocarbon group.
[0035] R 2 R is preferably a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer, which is a fluorine-containing hydrocarbon group having 1 to 10 carbon atoms. 2 At least a part of the hydrogen atoms in the hydrocarbon group may be substituted with fluorine atoms, or all of the hydrogen atoms in the hydrocarbon group may be substituted with fluorine atoms.
[0036] Examples of fluorine-containing (meth)acrylic acid ester monomers include 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3,3-pentafluoropropyl (meth)acrylate, 2-(perfluorobutyl)ethyl (meth)acrylate, 3-(perfluorobutyl)-2-hydroxypropyl (meth)acrylate, 2-(perfluorohexyl)ethyl (meth)acrylate, 3-perfluorohexyl-2-hydroxypropyl (meth)acrylate, and 3-(perfluoro-3-methylbutyl)-2-hydroxypropyl (meth)acrylate. Examples of the fluorine-containing (meth)acrylic acid ester monomer include 1H,1H,3H-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, 1H,1H,7H-dodecafluoroheptyl (meth)acrylate, 1H-1-(trifluoromethyl)trifluoroethyl (meth)acrylate, 1H,1H,3H-hexafluorobutyl (meth)acrylate, 1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl (meth)acrylate, and 2-(perfluorooctyl)ethyl (meth)acrylate. One type of fluorine-containing (meth)acrylic acid ester monomer may be used alone, or two or more types may be used in combination at any ratio.
[0037] The content of structural units derived from fluorine-containing (meth)acrylic acid ester monomers contained in the organic resin is preferably more than 20% by mass, more preferably 22% by mass or more, even more preferably 25% by mass or more, and even more preferably 30% by mass or more, when the total monomer components constituting the organic resin are taken as 100% by mass. Also, it is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less, even more preferably 40% by mass or less, and most preferably 35% by mass or less. By setting it within the above range, it becomes easy to be unevenly distributed on the surface layer, and sufficient dry adhesion and wet adhesion to the electrode are obtained.
[0038] Whether or not an organic resin contains a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer, and further the content of the structural unit derived from a fluorine (containing) (meth)acrylic acid ester monomer in the organic resin, can be measured using known methods. For example, first, a porous layer is removed from a porous film using an organic solvent such as water or alcohol, and the organic solvent such as water or alcohol is thoroughly dried to obtain the components contained in the porous layer. An organic solvent that dissolves the organic resin components is added to the obtained components to dissolve only the organic resin components. Next, the organic solvent is dried from the solution in which the organic resin components have been dissolved, and only the organic resin components are extracted. The obtained organic resin components are used to perform nuclear magnetic resonance ( 1 H-NMR, 19 F-NMR, 13 It can be calculated from the signal intensity indicating the fluorine-containing (meth)acrylic acid ester monomer by C-NMR), infrared absorption spectroscopy (IR), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence analysis (EDX), elemental analysis, pyrolysis gas chromatography mass spectrometer (pyrolysis GC / MS), etc. In particular, after confirming the presence or absence of the fluorine-containing (meth)acrylic acid ester monomer by pyrolysis GC / MS, 13 The content of structural units derived from the fluorine-containing (meth)acrylic acid ester monomer can be determined by C-NMR (a solid-state NMR sample tube is filled with the organic resin component and an appropriate amount of solvent (deuterated chloroform), and after leaving it to stand overnight, measurement is performed by the DD / MAS method).
[0039] The number of fluorine atoms in the fluorine-containing (meth)acrylic acid ester constituting the fluorine-containing (meth)acrylic acid ester monomer is preferably 3 or more and 13 or less. More preferably, it is 3 or more and 11 or less, and even more preferably, it is 3 or more and 9 or less. By setting it in the above range, it is possible to achieve both low surface free energy and coatability of the organic resin. When the number of fluorine atoms is 3 or more, the surface free energy of the organic resin is sufficiently reduced, and the dry adhesion and wet adhesion to the electrode are sufficient. When the number of fluorine atoms is 13 or less, the coatability to the porous substrate is ensured, and productivity is improved.
[0040] The number of fluorine atoms in the fluorine-containing (meth)acrylic acid ester can be measured using known methods. For example, first, the porous layer is removed from the porous film using an organic solvent such as water and alcohol, and the organic solvent such as water and alcohol is thoroughly dried to obtain the components contained in the porous layer. An organic solvent that dissolves the organic resin components is added to the obtained components to dissolve only the organic resin components, which are then separated from the inorganic particles. Next, the organic solvent is dried from the solution in which the organic resin components have been dissolved, and only the organic resin components are extracted. The obtained organic resin components are used to perform nuclear magnetic resonance ( 1 H-NMR, 19 F-NMR, 13 It can be calculated from the signal intensity showing the fluorine-containing (meth)acrylic acid ester monomer by C-NMR), infrared absorption spectroscopy (IR), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence spectroscopy (EDX), elemental analysis, pyrolysis gas chromatography mass spectrometer (pyrolysis GC / MS), etc. Among these, pyrolysis GC / MS is particularly useful.
[0041] The organic resin preferably has a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer and a structural unit derived from a (meth)acrylic acid ester monomer having two or more reactive groups per molecule. The organic resin may be a copolymer of a polymer polymerized using at least a fluorine-containing (meth)acrylic acid ester monomer and a polymer polymerized using, for example, a plurality of types of (meth)acrylic acid ester monomers. Preferred (meth)acrylic acid ester monomers include a (meth)acrylic acid ester monomer having two or more reactive groups per molecule, a (meth)acrylic acid ester monomer containing at least one cyclic hydrocarbon group, and a (meth)acrylic acid ester monomer having a hydroxyl group. By containing a (meth)acrylic acid ester monomer having two or more reactive groups per molecule, a polymer having excellent electrolyte resistance with suppressed swelling in the electrolyte, and excellent dry adhesion and wet adhesion to the electrode can be obtained.
[0042] By forming a copolymer consisting of (meth)acrylic acid ester monomers having two or more reactive groups per molecule, a crosslinked structure can be formed during polymerization. Examples of (meth)acrylic acid ester monomers having two or more reactive groups per molecule include allyl (meth)acrylate, ethylene di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, trimethylolpropane-tri(meth)acrylate, polyalkylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,12-dodecyldiol di(meth)acrylate, and urethane acrylate. Among them, it is more preferable to use a (meth)acrylate containing an alkyldiol group having 6 or more carbon atoms, since this improves the dry adhesion and wet adhesion to the electrode as well as the battery characteristics (rate). The upper limit of the carbon number is not particularly limited, but it is preferably 15 or less.
[0043] The content of structural units derived from (meth)acrylic acid ester monomers having two or more reactive groups per molecule contained in the organic resin is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, even more preferably 3.0% by mass or more, and even more preferably 5.0% by mass or more, when the total monomer components constituting the organic resin are taken as 100% by mass. Also, it is preferably less than 10.0% by mass, more preferably 9.0% by mass or less, and even more preferably 7.0% by mass or less. By setting it in the above range, excellent resistance to electrolyte with suppressed swelling in electrolyte, and sufficient dry adhesion and wet adhesion to the electrode can be obtained.
[0044] The organic resin preferably has a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer and a structural unit derived from a (meth)acrylic acid ester monomer having two or more reactive groups per molecule, and further has a structural unit derived from at least one cyclic hydrocarbon group-containing (meth)acrylic acid ester monomer. Examples of such organic resins include a copolymer of a polymer polymerized using a fluorine-containing (meth)acrylic acid ester monomer and a polymer consisting of a (meth)acrylic acid ester monomer having two or more reactive groups per molecule, and further a polymer consisting of at least one cyclic hydrocarbon group-containing (meth)acrylic acid ester monomer. Examples of the at least one cyclic hydrocarbon group-containing (meth)acrylic acid ester monomer include benzyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, and 3,4-epoxycyclohexylmethyl (meth)acrylate.
[0045] The content of structural units derived from at least one cyclic hydrocarbon group-containing (meth)acrylic acid ester monomer contained in the organic resin is preferably 20% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more, when the total monomer components constituting the organic resin are taken as 100% by mass. Also, it is preferably less than 70% by mass, more preferably 65% by mass or less, and even more preferably 60% by mass or less. By setting it within the above range, stability during polymerization is improved, and further swelling in the electrolyte is suppressed, resulting in excellent electrolyte resistance, and sufficient dry adhesion and wet adhesion to the electrode can be obtained.
[0046] The organic resin may further contain a structural unit derived from a (meth)acrylic acid ester monomer having a hydroxyl group, which adjusts the glass transition temperature of the organic resin and provides excellent dry and wet adhesion to the electrodes.
[0047] Examples of (meth)acrylic acid ester monomers having a hydroxyl group include hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 7-hydroxyheptysil (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate. The (meth)acrylic acid ester monomers having a hydroxyl group may be used alone or in combination of two or more at any ratio. In particular, hydroxyethyl acrylate (HEA), 4-hydroxybutyl acrylate (4-HBA), and 2-hydroxypropyl acrylate (2-HPA) are preferred.
[0048] The content of structural units derived from (meth)acrylic acid ester monomers having hydroxyl groups contained in the organic resin is 5.0% by mass or less, when the total components of the organic resin are taken as 100% by mass. It is preferably 3.0% by mass or less, more preferably 2.0% by mass or less, even more preferably 1.5% by mass or less, and even more preferably 1.0% by mass or less. By making the content of (meth)acrylic acid ester monomers having hydroxyl groups contained in the organic resin 5.0% by mass or less, sufficient dry adhesion with the electrode can be obtained, and by suppressing swelling in the electrolyte, sufficient wet adhesion with the electrode can be obtained, thereby improving the battery characteristics.
[0049] The content of the structural unit derived from the (meth)acrylic acid ester monomer having two or more reactive groups per molecule contained in the organic resin, the structural unit derived from the (meth)acrylic acid ester monomer containing at least one cyclic hydrocarbon group, and the structural unit derived from the (meth)acrylic acid ester monomer having a hydroxyl group can be measured using a known method. For example, first, the porous layer is removed from the porous film using an organic solvent such as water or alcohol, and the organic solvent such as water or alcohol is thoroughly dried to obtain the components contained in the porous layer. An organic solvent that dissolves the organic resin components is added to the obtained components to dissolve only the organic resin components. Next, the organic solvent is dried from the solution in which the organic resin components are dissolved, and only the organic resin components are extracted. The obtained organic resin components are used to perform nuclear magnetic resonance ( 1 H-NMR, 19 F-NMR, 13 It can be calculated from the signal intensity showing the (meth)acrylic acid ester monomer having a hydroxyl group by using 1C-NMR), infrared absorption spectroscopy (IR), X-ray photoelectron spectroscopy (XPS), X-ray fluorescence spectroscopy (EDX), elemental analysis, pyrolysis gas chromatography mass spectrometer (pyrolysis GC / MS), etc. In particular, after confirming the presence or absence of a structural unit derived from a (meth)acrylic acid ester monomer having two or more reactive groups per molecule, a structural unit derived from at least one cyclic hydrocarbon group-containing (meth)acrylic acid ester monomer, and a structural unit derived from a (meth)acrylic acid ester monomer having a hydroxyl group by pyrolysis GC / MS, 13 The contents of structural units derived from (meth)acrylic acid ester monomers having two or more reactive groups per molecule, structural units derived from (meth)acrylic acid ester monomers containing at least one cyclic hydrocarbon group, and structural units derived from (meth)acrylic acid ester monomers having a hydroxyl group can be determined by C-NMR (a solid-state NMR sample tube is filled with the organic resin component and an appropriate amount of a solvent (deuterated chloroform), allowed to stand overnight, and then measured by a DD / MAS method).
[0050] The copolymer can be obtained, for example, by emulsion polymerization of a plurality of (meth)acrylic acid ester monomers in an aqueous medium. The conditions of the emulsion polymerization are not particularly limited, and for example, the reaction may be carried out in an aqueous medium in the presence of an emulsifier and a polymerization initiator, preferably at a temperature of about 50 to 100°C for about 1 to 30 hours. If necessary, a chain transfer agent, a chelating agent, a pH adjuster, a solvent, etc. may be added.
[0051] As the emulsifier, anionic surfactants, nonionic surfactants, a combination of anionic surfactants and nonionic surfactants, etc., can be used. In some cases, amphoteric surfactants or cationic surfactants can also be used.
[0052] Examples of the anionic surfactant include sodium alkyl sulfate, sodium alkylbenzene sulfonate, sodium succinate dialkyl ester sulfonate, sodium alkyl diphenyl ether disulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, etc. Among these, sodium lauryl sulfate, sodium dodecylbenzene sulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium lauryl sulfate, etc. are preferred.
[0053] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylaryl ethers, polyoxyethylene fatty acid esters, polyoxyethylene sorbitan fatty acid esters, etc. In general, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, etc. are used.
[0054] Examples of amphoteric surfactants include lauryl betaine, sodium hydroxyethyl imidazoline sulfate, and sodium imidazoline sulfonate.
[0055] Examples of the cationic surfactant include alkylpyridinium chloride, alkyltrimethylammonium chloride, dialkyldimethylammonium chloride, and alkyldimethylbenzylammonium chloride.
[0056] In addition, as the emulsifier, fluorine-based surfactants such as perfluoroalkyl carboxylates, perfluoroalkyl sulfonates, perfluoroalkyl phosphates, perfluoroalkyl polyoxyethylenes, perfluoroalkyl betaines, and perfluoroalkoxy fluoroammonium carboxylates can also be used.
[0057] Furthermore, so-called reactive emulsifiers copolymerizable with the above-mentioned monomers can be used, such as sodium styrenesulfonate, sodium allyl alkylsulfonate, ammonium polyoxyethylene alkyl allyl phenyl ether sulfate, polyoxyethylene alkyl allyl phenyl ether, etc. In particular, a combination of ammonium 2-(1-allyl)-4-nonylphenoxy polyethylene glycol sulfate and 2-(1-allyl)-4-nonylphenoxy polyethylene glycol is preferred.
[0058] The amount of emulsifier used is preferably 0.05% by mass or more and 10% by mass per 100% by mass of the total amount of the monomer mixture. The lower limit is more preferably 0.5% by mass or more, and even more preferably 1.5% by mass or more. The upper limit is more preferably 7% by mass or less, and even more preferably 3% by mass or less. By setting the amount within the above range, when the organic resin is made into a particle shape, it is possible to adjust the average particle size to an appropriate value, and it is also possible to suppress interactions with inorganic particles and binders described later, which makes it easier for the organic resin to be unevenly distributed on the surface, resulting in good dry adhesion and wet adhesion to the electrode.
[0059] In addition to the organic resin having adhesiveness to the electrode, another organic resin having a different function may be included. The organic resin having a different function may be used as an emulsion binder to bond organic resins together or to bond an organic resin to inorganic particles, or to provide a binder function to bond an organic resin to a porous substrate. The binder function improves adhesion, and the adhesion to the electrode can be further improved. As the organic resin, a resin that is electrochemically stable within the range of use of the battery is preferable.
[0060] The organic resin preferably contains organic resin particles. By using organic resin particles, uneven distribution of the organic resin on the surface of the porous layer can be promoted. In the present invention, the organic resin particles include those having a particle shape, as well as those partially forming a film and fused with surrounding particles and binders. The shape is preferably spherical from the viewpoint of adjusting the arithmetic mean height (Sa) in a 2200 μm square of the porous layer to an appropriate range.
[0061] When an organic resin having a particle shape is selected, the average particle size of the particles is preferably 100 nm or more and 500 nm or less. The lower limit is more preferably 120 nm or more, even more preferably 150 nm or more, and most preferably 170 nm or more. The upper limit is more preferably 400 nm or less, even more preferably 300 nm or less, and most preferably 250 nm or less. By setting it in the above range, it is possible to adjust the arithmetic mean height (Sa) of the porous layer in a 2200 μm square to an appropriate range, and the battery characteristics are further improved. The average particle size of the organic resin particles can be adjusted by changing the type of emulsifier and the monomer composition ratio during polymerization of the organic resin particles.
[0062] (2) Inorganic particles The porous layer in the present invention contains inorganic particles. By containing inorganic particles, the porous layer can provide thermal dimensional stability and suppress short circuits caused by foreign matter. In addition, by containing inorganic particles, when the maximum value of the surface elastic modulus of the porous layer is α in 50 measurements of the surface elastic modulus, α corresponds to the inorganic particles.
[0063] When aluminum oxide is used as an inorganic particle in an embodiment in which both inorganic particles and organic particles are contained in the porous layer as in the present invention, it has somewhat inferior characteristics in terms of wear of parts during the dispersion process of organic resin and inorganic particles and wear of parts during the coating process of the porous layer. Therefore, the inorganic particles contained in the porous layer are specifically preferred examples of inorganic oxide particles such as boehmite, silica, titanium oxide, zirconium oxide, iron oxide, magnesium oxide, etc., inorganic nitride particles such as aluminum nitride and silicon nitride, and poorly soluble ion crystal particles such as calcium fluoride, barium fluoride, and barium sulfate. Among them, boehmite, barium sulfate, and magnesium oxide, which are effective in reducing wear of parts during the dispersion process of organic resin particles and inorganic particles, are particularly preferred. Furthermore, these inorganic particles may be used alone or in a mixture of two or more types.
[0064] The shape of the inorganic particles used may be spherical, cubic, rectangular, needle-like, rod-like, elliptical, irregular, etc. Among these, from the viewpoints of surface modification, dispersibility, and coatability, and from the viewpoint of adjusting the arithmetic mean height (Sa) of the porous layer in a 2200 μm square to an appropriate range, spherical and cubic shapes are preferred.
[0065] The average particle size of the inorganic particles is preferably 0.3 μm or more and 1.2 μm or less. The lower limit is more preferably 0.5 μm or more, and even more preferably 0.7 μm or more. The upper limit is more preferably 1.0 μm or less, and even more preferably 0.8 μm or less. By setting the average particle size in the above range, it is possible to obtain an appropriate porous structure and adjust the arithmetic mean height (Sa) of the porous layer in a 2200 μm square to an appropriate range, thereby further improving the battery characteristics.
[0066] The mass content of the inorganic particles contained in the porous layer is preferably 50% by mass or more and 95% by mass or less with respect to the entire porous layer. The lower limit is more preferably 60% by mass or more, and even more preferably 70% by mass or more. The upper limit is more preferably 90% by mass or less, and even more preferably 85% by mass or less. By setting the mass content of the inorganic particles contained in the porous layer within the above range, sufficient thermal dimensional stability and dry and wet adhesion to the electrodes can be obtained.
[0067] (3) Binder The porous layer of the present invention may contain a binder in order to make the organic resin and inorganic particles constituting the porous layer adhere to each other and to make the organic resin and inorganic particles adhere to the porous substrate. As the binder, a resin that is electrochemically stable within the range of use of the battery is preferable. In addition, the binder may be a binder that is soluble in an organic solvent, a water-soluble binder, an emulsion binder, etc., and may be used alone or in combination.
[0068] When using a binder soluble in an organic solvent or a water-soluble binder, the preferred viscosity of the binder itself is 10,000 mPa·s or less when the concentration is 15% by mass. More preferably, it is 8,000 mPa·s or less, and even more preferably, it is 5,000 mPa·s or less. By keeping the viscosity at 10,000 mPa·s or less at a concentration of 15% by mass, it is possible to suppress an increase in the viscosity of the coating material, and the organic resin is unevenly distributed on the surface, improving the dry adhesion to the electrode.
[0069] In addition, when an emulsion binder is used, the dispersant may be water or an organic solvent, such as an alcohol solvent such as ethanol, or a ketone solvent such as acetone, but a water dispersion is preferred in terms of ease of handling and mixability with other components. The particle size of the emulsion binder is 30 to 1000 nm, preferably 50 to 500 nm, more preferably 70 to 400 nm, and even more preferably 80 to 300 nm. By setting the particle size of the emulsion binder to 30 nm or more, the increase in air permeability can be suppressed, and the battery characteristics become good. Furthermore, by setting the particle size to 1000 nm or less, sufficient adhesion between the porous layer and the porous substrate can be obtained.
[0070] Examples of the resin used in the binder include polyamide, polyamideimide, polyimide, polyetherimide, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polysulfone, polyketone, polyetherketone, polycarbonate, polyacetal, polyvinyl alcohol, polyethylene glycol, cellulose ether, acrylic resin, polyethylene, polypropylene, polystyrene, and urethane. Among these, acrylic resin is particularly preferred because it can provide stronger adhesion due to the interaction with the organic resin. These resins may be used alone or in a mixture of two or more as necessary.
[0071] When a water-soluble binder is used, the amount added is preferably 0.5% by mass or more, based on the total amount of the organic resin and the inorganic particles. More preferably, it is 1% by mass or more, and even more preferably, it is 1.5% by mass or more. Also, it is preferably 10% by mass or less. More preferably, it is 8% by mass or less, and even more preferably, it is 6% by mass or less. By setting the amount of the water-soluble binder to 0.5% by mass or more, sufficient adhesion between the porous layer and the porous substrate can be obtained. Also, by setting it to 10% by mass or less, it is possible to suppress an increase in air permeability, and the battery characteristics become good.
[0072] When an emulsion binder is used, the amount of the emulsion binder added is preferably 1% by mass or more based on the total amount of the organic resin and the inorganic particles. More preferably, the amount of the emulsion binder added is 5% by mass or more, even more preferably, 7.5% by mass or more, and most preferably, 10% by mass or more. Also, the amount of the emulsion binder added is preferably 30% by mass or less, more preferably, 25% by mass or less, and even more preferably, 20% by mass or less. By setting the amount of the emulsion binder added to 1% by mass or more, sufficient adhesion between the porous layer and the porous substrate can be obtained. Also, by setting the amount of the emulsion binder added to 30% by mass or less, the increase in air permeability can be suppressed, and the battery characteristics become good. In particular, by setting the amount of the emulsion binder added to 7.5% by mass or more and 20% by mass or less, not only is the adhesion between the organic resin and the inorganic particles and the adhesion of these particles to the substrate promoted, but also the organic resin is interacted with the inorganic particles, and the dry adhesion and wet adhesion to the electrode are improved.
[0073] (4) Formation of porous layer A method for forming the porous layer will be described below.
[0074] The porous layer may be formed through a two-stage coating process or a one-stage coating process. When it is formed through a two-stage coating process, a coating layer containing inorganic particles is formed in the first stage, and a coating layer containing an organic resin is formed in the second stage. Having a coating liquid containing an organic resin on the surface layer makes it easy to ensure adhesion to the electrode. In this case, the coating layer containing the organic resin can be made thin, or the amount of organic resin can be reduced to the extent that it is present locally on the surface, making it possible to reduce costs.
[0075] The two-stage coating process is a method in which a coating liquid consisting of inorganic particles and a solvent is prepared, the coating liquid is applied onto a porous substrate, the solvent of the coating liquid is dried, and then a coating liquid consisting of an organic resin and a solvent is prepared, the coating liquid is applied onto the inorganic particle coating layer, and the solvent of the coating liquid is dried to form a porous layer, thereby obtaining a porous film. Spray coating may be used as the coating method.
[0076] The one-step coating process is a method in which a coating liquid consisting of an organic resin, inorganic particles and a solvent is prepared, coated onto a porous substrate, and the solvent in the coating liquid is dried to form a porous layer, thereby obtaining a porous film.
[0077] The coating method is not particularly limited, but the latter method allows for cost reduction by reducing the number of coating steps, and therefore the method for forming the porous layer by the latter method will be described below.
[0078] (i) First, the organic resin is dispersed to a predetermined concentration to prepare a coating liquid. The coating liquid is prepared by dispersing, suspending, or emulsifying the organic resin in a solvent. The solvent for the aqueous dispersion coating liquid is not necessarily limited, but is not particularly limited as long as it does not dissolve water or the organic resin and can disperse, suspend, or emulsify in a solid state. For example, organic solvents such as methanol, ethanol, 2-propanol, acetone, tetrahydrofuran, methyl ethyl ketone, ethyl acetate, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, and dimethylformamide can be mentioned. From the viewpoints of low environmental load, safety, and economics, an aqueous emulsion in which an organic resin is emulsified in water or a mixture of water and alcohol is preferred. When water is used, a solvent other than water may be further added.
[0079] The solids concentration of the coating fluid is preferably 5% or more and 40% or less. By setting it within the specified range, both coating stability and surface uneven distribution during coating and drying can be achieved. Furthermore, the solution viscosity of the coating fluid is preferably 5 mPa·s or more and 50 mPa·s or less. By setting it within the specified range, both dispersibility of the coating fluid and surface uneven distribution during coating and drying can be achieved. By adjusting the solids concentration of the coating fluid to be low and the viscosity to be low within the above-mentioned preferred range, the organic resin can be adjusted to be unevenly distributed in the outer layer.
[0080] If necessary, a film-forming assistant, a dispersant, a thickener, a stabilizer, an antifoaming agent, a leveling agent, etc. may be added to the coating liquid.
[0081] Examples of the method for dispersing the coating liquid include a ball mill, a bead mill, a sand mill, a roll mill, a homogenizer, an ultrasonic homogenizer, a high-pressure homogenizer, an ultrasonic device, and a paint shaker. Among these, by selecting a dispersing method (bead mill, sand mill) that exerts high pressure on the inorganic particles and the organic resin during dispersion, the dispersibility is improved, and the organic resin is more likely to be unevenly distributed on the surface. A combination of these mixing and dispersing machines may be used to perform dispersion in stages.
[0082] (ii) Next, the obtained coating liquid is applied onto a porous substrate. Examples of the coating method include dip coating, gravure coating, slit die coating, knife coating, comma coating, kiss coating, roll coating, bar coating, spray coating, immersion coating, spin coating, screen printing, inkjet printing, pad printing, and other types of printing. The coating method is not limited to these, and may be selected according to the preferred conditions of the organic resin, binder, dispersant, leveling agent, solvent, substrate, etc. used.
[0083] (iii) After that, the solvent of the coating liquid is dried to form a porous layer. The drying temperature is preferably 40°C or more and 100°C or less. This allows the porous layer to dry uniformly, the thickness of the porous layer to be uniform, and the adhesion to the electrode to be improved. If the temperature is less than 40°C, the solvent of the coating liquid does not dry. On the other hand, if the temperature is higher than 100°C, the amount of heat during drying increases, and the particle shape cannot be maintained and a film is formed, so that the organic resin particles do not become unevenly distributed on the surface, and β / α>1. Therefore, by setting the ratio within the specified range, it is possible to achieve both good adhesion to the electrode and low costs due to improved coating and drying speed.
[0084] The thickness of the porous layer is preferably 2.0 μm or more. More preferably, it is greater than 3.0 μm, and even more preferably, it is 4.0 μm or more. Also, it is preferably 8.0 μm or less. More preferably, it is 7.0 μm or less, and even more preferably, it is 6.0 μm or less. The thickness of the porous layer here means the thickness of the porous layer in the case of a porous film having a porous layer on one side of a porous substrate, and means the sum of the thicknesses of both porous layers in the case of a porous film having a porous layer on both sides of a porous substrate. By making the thickness of the porous layer 2.0 μm or more, sufficient thermal dimensional stability and adhesion to the electrode can be obtained. Also, by making it 8.0 μm or less, a porous structure is formed, and the battery characteristics are good. Also, it may be advantageous in terms of cost.
[0085] [Porous base material] In the present invention, the porous substrate has a structure in which micropores are formed inside and these micropores are connected from one surface to the other surface. Examples of the porous substrate include a microporous membrane, a nonwoven fabric, and a porous membrane sheet made of a fibrous material. The material constituting the porous substrate is preferably made of a resin that is electrically insulating, electrically stable, and stable in an electrolyte. In addition, from the viewpoint of providing a shutdown function, the resin used is preferably a thermoplastic resin having a melting point of 200° C. or less. The shutdown function here refers to a function that, when a lithium ion battery generates abnormal heat, closes the porous structure by melting with heat, stops ion movement, and stops discharge.
[0086] Examples of thermoplastic resins include polyolefin-based resins, and the porous substrate is preferably a polyolefin-based porous substrate.More preferably, the polyolefin-based porous substrate has a melting point of 200°C or less.Specific examples of polyolefin-based resins include polyethylene, polypropylene, ethylene-propylene copolymers, and mixtures of these resins, and examples of such resins include a single-layer porous substrate containing 90% by mass or more of polyethylene, and a multi-layer porous substrate made of polyethylene and polypropylene.
[0087] Next, a method for producing a porous substrate will be described. Although the method for producing a porous substrate is not particularly limited, a method for producing a polyolefin microporous membrane will be described below.
[0088] (a) First, a plasticizer is added to the resin composition made of the above-mentioned polyolefin in a twin-screw extruder, and the mixture is melt-kneaded to prepare a resin solution.
[0089] The polyolefin resin composition is composed of a polyolefin resin, and may be a single composition or a mixture of two or more kinds of polyolefin resins. Examples of polyolefin resins include, but are not limited to, polyethylene and polypropylene. As the polyethylene resin, ultra-high molecular weight polyethylene, high density polyethylene, and medium density polyethylene low density may be used as a single composition or may be a mixture of different molecular weights. It is preferable to use a mixture of two or more kinds of polyethylene selected from the group consisting of ultra-high molecular weight polyethylene, high density polyethylene, medium density polyethylene, and low density polyethylene, and in particular, a mixture of two or more kinds of polyethylene selected from the group consisting of ultra-high molecular weight polyethylene, high density polyethylene, medium density polyethylene, and low density polyethylene having a weight average molecular weight (Mw) of 1×10 6 Ultra-high molecular weight polyethylene (A) with Mw of 1×10 4 More than 9×10 4 Preferably, the mixture comprises polyethylene (B) having a Mw of less than 1×10 6 It is more preferable that the polymer contains the ultra-high molecular weight polyethylene having a molecular weight of 100% or more. The blending ratio of (A) and (B) is preferably such that the content of (A) is 50% by mass or more, with the total of (A) and (B) being 100% by mass.
[0090] Since the plasticizer allows for relatively high-ratio stretching, the solvent is preferably liquid at room temperature. Examples of the solvent include aliphatic solvents such as nonane, decane, decalin, paraxylene, undecane, dodecane, and liquid paraffin. The blending ratio of the polyolefin resin composition and the plasticizer is preferably 10% by mass or more and 50% by weight or less of the polyolefin resin composition. (b) Next, the resin solution is fed from the extruder to a die, extruded into a sheet and cooled to form a gel-like sheet.
[0091] (c) Thereafter, the gel-like sheet is stretched. The gel-like sheet is preferably stretched at a predetermined stretch ratio by a tenter method, a roll method, an inflation method, or a combination of these.
[0092] (d) Thereafter, the plasticizer is removed using a washing solvent, and the resulting mixture is dried to obtain a microporous polyolefin membrane.
[0093] (e) In addition to the above steps, stretching (also called dry re-stretching) may be performed after the drying step. The second stretching can be performed by a tenter method or the like while heating the polyolefin microporous membrane in the same manner as the above-mentioned stretching. The re-stretching ratio is preferably 1.01 to 2.0 times in the case of uniaxial stretching, and preferably 1.01 to 2.0 times in the case of biaxial stretching.
[0094] The thickness of the porous substrate is preferably 3 μm or more and 50 μm or less, more preferably 5 μm or more and 30 μm or less. By making the thickness of the porous substrate 50 μm or less, an increase in the internal resistance of the porous substrate can be suppressed. In addition, by making the thickness of the porous substrate 3 μm or more, it becomes possible to manufacture the porous substrate, and sufficient mechanical properties can be obtained.
[0095] The thickness of the porous substrate can be measured by observing the cross section with a microscope. When a porous layer is laminated, the vertical distance between the interface between the porous substrate and the porous layer is measured as the thickness of the porous substrate. Five pieces of 100 mm x 100 mm in size are cut out, and the central part of each of the five samples is observed and measured, and the average value is taken as the thickness of the porous substrate.
[0096] The air permeability of the porous substrate is preferably 50 sec / 100cc or more and 1,000 sec / 100cc or less. More preferably, it is 50 sec / 100cc or more and 500 sec / 100cc or less. By making the air permeability 50 sec / 100cc or more, sufficient mechanical properties can be obtained. In addition, by making the air permeability 1,000 sec / 100cc or less, sufficient ion mobility can be obtained, resulting in good battery properties.
[0097] [Secondary battery] The porous film of the present embodiment can be suitably used as a separator for secondary batteries such as lithium ion batteries. A lithium ion battery has a configuration in which a secondary battery separator and an electrolyte are interposed between a positive electrode in which a positive electrode active material is laminated on a positive electrode current collector and a negative electrode in which a negative electrode active material is laminated on a negative electrode current collector.
[0098] The positive electrode is a positive electrode material consisting of an active material, a binder resin, and a conductive assistant layered on a current collector. Examples of the active material include layered lithium-containing transition metal oxides such as LiCoO2, LiNiO2, and Li(NiCoMn)O2, spinel-type manganese oxides such as LiMn2O4, and iron-based compounds such as LiFePO4. As the binder resin, a resin with high oxidation resistance may be used. Specific examples include fluororesin, acrylic resin, and styrene-butadiene resin. Carbon materials such as carbon black and graphite are used as the conductive assistant. Metal foil is suitable as the current collector, and aluminum foil is often used in particular.
[0099] The negative electrode is a current collector on which negative electrode materials consisting of active materials and binder resins are laminated. The active materials include carbon materials such as artificial graphite, natural graphite, hard carbon, and soft carbon, lithium alloy materials such as tin and silicon, metal materials such as Li, and lithium titanate (Li4Ti5O 12 ) and the like. As the binder resin, fluororesin, acrylic resin, styrene-butadiene resin, and the like are used. As the current collector, a metal foil is suitable, and in particular, copper foil is often used.
[0100] The electrolyte is a place where ions move between the positive and negative electrodes in the secondary battery, and is composed of an electrolyte dissolved in an organic solvent. Examples of the electrolyte include LiPF6, LiBF4, and LiClO4, and LiPF6 is preferably used from the viewpoint of solubility in organic solvents and ionic conductivity. Examples of the organic solvent include ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, and two or more of these organic solvents may be mixed and used.
[0101] In the method of producing a secondary battery, first, an active material and a conductive assistant are dispersed in a binder resin solution to prepare an electrode coating solution, and the coating solution is applied onto a current collector, and the solvent is dried to obtain a positive electrode and a negative electrode. The thickness of the coating film after drying is preferably 50 μm to 500 μm. A separator for a secondary battery is placed between the obtained positive electrode and negative electrode so as to contact the active material layer of each electrode, and the separator is enclosed in an exterior material such as an aluminum laminate film. After injecting an electrolyte, a negative electrode lead and a safety valve are installed, and the exterior material is sealed. The secondary battery obtained in this way has high adhesion between the electrode and the separator for a secondary battery, has excellent high-rate characteristics, and can be manufactured at low cost.
[0102] Taking advantage of its characteristics, the secondary battery of the present invention can be suitably used in vehicles, unmanned transport vehicles, electronic devices, or power storage devices. EXAMPLES
[0103] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. Measurement methods used in the examples are as follows.
[0104] [Measurement method] (1) Surface elastic modulus: maximum value α, minimum value β, α / β The surface elastic modulus of the porous film was measured using a Bruker AXS AFM (Dimension icon (manufactured since 2006)). The measurement mode was set to Quantitative Nanomechanical Mapping, and a probe (Tap525) was used. After setting the spring constant and probe tip curvature of the probe using a sample with a known elastic modulus, the surface elastic modulus of the porous layer was measured in a measurement range of 10 nm. Measurements were performed at 50 locations randomly selected from each 5 cm x 5 cm sample, and the maximum value was taken as α and the minimum value as β. α / β was then calculated from α and β.
[0105] (2) The arithmetic mean height (Sa) of the porous layer in an area of 2200 μm square A sample cut to 5 cm x 5 cm from the porous film was attached to a metal frame with outer dimensions of 6 cm square and inner dimensions of 3 cm square without wrinkles. Using a scanning white light interference microscope VS-1540 manufactured by Hitachi High-Tech Science Corporation, the surface roughness was measured under the following conditions, and the three-dimensional surface roughness parameter (Sa) was calculated in accordance with ISO 25178. Under the same conditions, measurements were performed on both surfaces of the porous film at four points on each side, for a total of eight points, and the measured values were averaged. In addition, when a porous layer was provided on one side, the values measured at four points on the surface having the pores were averaged. Objective lens: 5x -Tube lens: 0.5x Wavelength filter: 530white Camera: High resolution Measurement mode: Wave Cutoff: None (3) Mass content of inorganic particles contained in the porous layer The porous layer was removed from a 10cm x 10cm porous film using 40g of water, and the water and organic solvents such as alcohol were thoroughly dried to obtain the components contained in the porous layer. After measuring the mass of all the components obtained, the components were burned at a high temperature at which the organic resin components melted and decomposed, and the mass of only the inorganic particles was measured. The mass content of the inorganic particles in the porous layer was calculated in mass% using the formula (mass of inorganic particles / mass of all components) x 100.
[0106] (4) Volume content γ of inorganic particles contained in the porous layer The components of the porous layer after desorption and drying obtained in (3) were separated into organic resin components and inorganic components using an appropriate organic solvent that dissolves only the organic resin components. The specific gravity of each component was measured with a specific gravity meter. The volume content of the inorganic particles in the porous layer was calculated in volume % from the mass content (mass %) of the inorganic particles and organic resin components obtained earlier and the specific gravity of the inorganic particles and organic resin components. The above measurement was performed on five samples, and the measured values were averaged.
[0107] (5) Occupancy rate δ of inorganic particles in the surface portion of the porous layer The surface of the porous layer of the porous film on which Pt / Pd was vapor-deposited for 30 seconds was measured with a SEM-EDX (Hitachi SE8200) at a magnification of 10,000 times and an accelerating voltage of 5.0 kV, and the inorganic elements of the inorganic particles were analyzed. Using image analysis software (Toyo Technica, SPIP6.0.10), the element symbol display, magnification display, scale bar, and accelerating voltage display in the EDX image were masked and removed, and then the detection method was performed in the "particle and pore analysis" mode with a threshold level of 130 nm, and the obtained area ratio was defined as the inorganic particle occupancy rate δ. The above measurement was performed on five samples, and the measured values were averaged.
[0108] (6) Surface free energy of the porous layer The contact angles of the surfaces of samples cut to 100 mm x 100 mm from the porous film were measured for water, ethylene glycol, methylene iodide, and formamide, and the surface free energy (mN / m) of the porous layer was measured using the Young-Dupre equation. The above measurements were performed on five samples, and the measured values were averaged.
[0109] (7) Thickness of the porous layer A cross section of the sample cut to 100 mm x 100 mm from the porous film was cut out at the center with a microtome, and the cross section was observed at a magnification of 10,000 times with a field emission scanning electron microscope (S-800 manufactured by Hitachi, Ltd., accelerating voltage 26 kV) to measure the distance from the interface with the porous substrate to the highest point on the surface. In the case of one side, only one side was measured, and in the case of both sides, both sides were measured, and the total was taken as the film thickness of the porous layer. Regarding the interface between the porous substrate and the porous layer, the location where the inorganic particles were no longer confirmed in the region where the inorganic particles were present was defined as the interface. The above measurement was performed on five samples, and the measured values were averaged.
[0110] (8) Heat shrinkage rate (thermal dimensional stability) The porous film was cut into three samples measuring 100 mm x 100 mm, and the midpoint of one side and the midpoint of the opposite side of each sample were marked, the length between the midpoints was measured, and the sample was heat-treated for 30 minutes under no tension in a hot air oven at 150°C. After the heat treatment, the length between the midpoints of the same points as before the heat treatment was measured, and the thermal shrinkage was calculated using the following formula. Heat shrinkage rate (%) = [(length between midpoints before heat treatment - length between midpoints after heat treatment) / (length between midpoints before heat treatment)] x 100 The calculations were performed at two places on one sample at the same time, and the average of all the values was taken as the thermal shrinkage rate (thermal dimensional stability), with less than 5% being rated as excellent, 5% to less than 10% being excellent, 10% to less than 20% being good, 20% to less than 40% being acceptable, and 40% or more being unacceptable.
[0111] (9) Dry adhesion to electrodes The negative electrode (width 20mm x length 70mm) was used as the electrode, with graphite as the active material, SBR (styrene-butadiene rubber) resin as the binder, and carbon black as the conductive additive. A porous film (width 25mm x length 80mm) was placed so that the ends of the electrode and the porous film were aligned and overlapped in the longitudinal direction, and the active material and the porous layer were in contact, and a test piece was prepared by bonding the electrode and the porous film under the conditions of 75℃ / 6MPa / 10 seconds. Next, the negative electrode side of the obtained test piece was attached to an acrylic plate with a thickness of 2mm. After that, the porous film was peeled off at 180° at a peeling speed of 300mm / min, and the average adhesive strength obtained was judged as the adhesive strength. Excellent adhesive strength: The electrode and porous film peeled off with greater force. Excellent adhesive strength: The electrode and porous film peeled off when subjected to strong force. Good adhesive strength: The electrode and porous film peeled off with a somewhat strong force. · Good adhesive strength: The electrode and porous film peeled off with a weak force. -Poor adhesive strength: The electrode and porous film peeled off with very little force.
[0112] (10) Wet adhesion to electrodes The negative electrode (20mm wide x 70mm long) was used as the electrode, with graphite as the active material, SBR (styrene-butadiene rubber) as the binder, and carbon black as the conductive additive. A porous film (25mm wide x 80mm long) was placed so that the ends of the electrode and the porous film overlapped in the length direction, and the active material and the porous layer were in contact, and a test piece was prepared by bonding the electrode and the porous film under the conditions of 75℃ / 6MPa / 10 seconds. The test piece was placed in an aluminum laminate film that was closed with three pieces to form a bag, and after the electrolyte injection process (1g of electrolyte was soaked into the porous film side of the test piece), the remaining side of the aluminum laminate film was sealed using a vacuum sealer. The electrolyte used here was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:diethyl carbonate = 1:1 (volume ratio) to a concentration of 1 mol / liter. Next, the test piece was heat-pressed again under the conditions of 90°C / 3MPa / 60 seconds. After that, the test piece was removed from the aluminum laminate film, the electrolyte on the surface of the test piece was wiped off, and the negative electrode side of the test piece was attached to an acrylic plate with a thickness of 2 mm. Then, the porous film was peeled off at 180° under the condition of a peeling speed of 300 mm / min, and the obtained average adhesive strength was judged as the adhesive strength. Excellent adhesive strength: The electrode and porous film peeled off with greater force. Excellent adhesive strength: The electrode and porous film peeled off when subjected to strong force. Good adhesive strength: The electrode and porous film peeled off with a somewhat strong force. · Good adhesive strength: The electrode and porous film peeled off with a weak force. -Poor adhesive strength: The electrode and porous film peeled off with very little force.
[0113] (11) Battery construction The positive electrode sheet was prepared by dispersing 96 parts by mass of Li(Ni5 / 10Mn2 / 10Co3 / 10)O2 as a positive electrode active material, 1.0 parts by mass each of acetylene black and graphite as a positive electrode conductive assistant, and 2 parts by mass of polyvinylidene fluoride as a positive electrode binder in N-methyl-2-pyrrolidone using a planetary mixer, applying the resulting positive electrode slurry onto aluminum foil, drying, and rolling (coating weight: 10.0 mg / cm2). This positive electrode sheet was cut into a size of 40 mm x 40 mm. At this time, the tab adhesive portion for current collection, which was not attached to the active material layer, was cut out to a size of 5 mm x 5 mm on the outside of the active material surface. An aluminum tab with a width of 5 mm and a thickness of 0.1 mm was ultrasonically welded to the tab adhesive portion. The negative electrode sheet was prepared by dispersing 98 parts by mass of natural graphite as a negative electrode active material, 1 part by mass of carboxymethylcellulose as a thickener, and 1 part by mass of styrene-butadiene copolymer as a negative electrode binder in water using a planetary mixer, applying the negative electrode slurry onto copper foil, drying, and rolling (coating weight: 6.6 mg / cm2). This negative electrode sheet was cut to 45 mm x 45 mm. At this time, the current collecting tab adhesive part without the active material layer was cut out to a size of 5 mm x 5 mm on the outside of the active material surface. A copper tab of the same size as the positive electrode tab was ultrasonically welded to the tab adhesive part. Next, a porous film was cut to 55 mm x 55 mm, and the positive electrode and negative electrode were stacked on both sides of the porous film so that the active material layer separated the porous film, and all the positive electrode coating parts were arranged to face the negative electrode coating parts to obtain an electrode group. Then, the positive electrode, the porous film, and the negative electrode were bonded by heat pressing at 75°C / 6MPa / 10 seconds. The positive electrode, the porous film, and the negative electrode were sandwiched between a single 90mm x 200mm aluminum laminate film, the long side of the aluminum laminate film was folded, and the two long sides of the aluminum laminate film were heat-sealed to form a bag. An electrolyte was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate: ethyl methyl carbonate = 3:7 (volume ratio) to a concentration of 1 mol / L. 1.5g of electrolyte was poured into the bag-shaped aluminum laminate film, and the short side of the aluminum laminate film was heat-sealed while impregnating it under reduced pressure.Thereafter, the battery was heat-pressed again under the conditions of 90° C. / 3 MPa / 60 seconds, and then subjected to initial charge / discharge and final charge / discharge to prepare a laminated battery.
[0114] (12) High rate characteristics The rate characteristics were tested according to the following procedure, and evaluated by the discharge capacity retention rate. Using the above laminated battery, the discharge capacity when discharged at 0.5C and at 10C at 25°C were measured, and the discharge capacity retention rate was calculated by (discharge capacity at 10C) / (discharge capacity at 0.5C)×100. Here, the charging conditions were constant current charging at 0.5C and 4.3V, and the discharging conditions were constant current discharging at 2.7V. Five laminated batteries were produced, and the average of the three measurement results after removing the results with the maximum and minimum discharge capacity retention rates was taken as the capacity retention rate. A discharge capacity retention rate of less than 40% was rated as unacceptable, 45% to less than 50% was rated as good, 50% to less than 55% was rated as excellent, and 55% or more was rated as excellent.
[0115] (13) Nail penetration resistance The positive electrode slurry and the negative electrode slurry described in (11) were formed on both sides of an aluminum foil and a copper foil, respectively, and the positive electrode, the negative electrode, and the porous film were cut out to the above size. The positive electrode, the porous film, the negative electrode, and the porous film were stacked in this order to obtain an electrode group in which 10 positive electrodes, 11 negative electrodes, and 12 porous films were stacked. A laminated battery was produced in the same manner as in (11) except that the amount of electrolyte was 4.5 g. Thereafter, a constant current charge of 0.5 C and 4.3 V was performed, and a nail penetration test specified in SAE J2464 was performed on the fully charged laminated battery, and the obtained results were judged as nail penetration resistance. Excellent nail penetration resistance: The shape of the laminated battery did not change and the temperature increase was less than 20°C. Excellent nail penetration resistance: The shape of the laminated battery did not change, and the temperature increase was between 20°C and 50°C. Good nail penetration resistance: The laminated battery swelled and the temperature rose between 50°C and 70°C. - Nail penetration resistance: The laminated battery swelled and the temperature rose between 70℃ and 100℃. - Nail penetration resistance was not possible: The laminated battery swelled and the temperature rose by 100°C or more.
[0116] Example 1 Dispersion A 120 parts of ion-exchanged water and 1 part of Adeka Reasorb SR-1025 (emulsifier manufactured by Adeka Corporation) were charged into a reactor, and stirring was started. 0.4 parts of 2,2'-azobis(2-(2-imidazolin-2-yl)propane) (manufactured by Wako Pure Chemical Industries, Ltd.) were added under a nitrogen atmosphere, and a monomer mixture consisting of 33% by mass of 2,2,2-trifluoroethyl methacrylate (3FMA), 5.0% by mass of ethylene glycol dimethacrylate (EGDMA), 55% by mass of benzyl methacrylate (BM), 3.0% by mass of 4-hydroxybutyl acrylate (4HBA), 4% by mass of perfluoroalkoxyfluoroammonium carboxylate (PFAFCA) as an emulsifier, and 115 parts of ion-exchanged water was continuously dropped at 60 ° C. for 2 hours, and polymerization treatment was performed for 4 hours after the end of the dropwise addition, to produce a dispersion A containing an organic resin (particle form, particle size 190 nm, glass transition temperature: 49 ° C.) consisting of a copolymer.
[0117] Dispersion B The inorganic particles were cubic boehmite particles with an average particle size of 0.7 μm. Water in the same amount as the inorganic particles was added as a solvent, and carboxymethyl cellulose was added as a dispersant in an amount of 1% by mass relative to the inorganic particles. Dispersion B was prepared by dispersing the particles in a bead mill.
[0118] Coating Fluid Dispersion A, dispersion B, and an acrylic emulsion binder were dispersed in water so that the volume content α of inorganic particles contained in the porous layer was 55% by volume, the volume content of organic resin particles A was 30% by volume, the volume content of the acrylic emulsion binder was 15% by volume, and the solid content concentration of the coating liquid was 20% by mass, and mixed with a stirrer. The viscosity of the resulting coating liquid was 15 mPa·s. The resulting coating liquid was applied to both sides of a polyethylene porous substrate (thickness 9 μm, air permeability 70 sec / 100 cc) using a #10 wire bar, and dried in a hot air oven (drying temperature setting 60° C.) for 1 minute, and the contained solvent was evaporated to form a porous layer, thereby obtaining a porous film of the present invention. Table 1 shows the types of monomers contained in the organic resins used in Examples 1 to 18, and the contents (mass%) of each monomer contained in the organic resin. Table 2 shows the form and particle size of the organic resin, the polymerization stability, the type, particle size, shape of the inorganic particles, and the volume content γ of the inorganic particles contained in the porous layer. Table 3 shows the maximum value α, minimum value β, and α / β of the surface elastic modulus of the porous layers obtained in Examples 1 to 18, the arithmetic mean height (Sa) of the porous layer in a 2200 μm square area, the inorganic particle occupancy δ and δ / γ in the surface part of the porous layer, the surface free energy, the film thickness of the porous layer, and the measurement results of the thermal dimensional stability, dry adhesion, wet adhesion, high rate characteristics, and nail penetration resistance of the porous films and batteries using the same.
[0119] (Examples 2 to 16) A porous film of the present invention was obtained in the same manner as in Example 1, except that the composition, particle size, and shape of the organic resin were as shown in Tables 1 and 2. Table 3 shows the measurement results of the porous layer, the porous film, and the battery using the same.
[0120] (Examples 17 to 18) A porous film of the present invention was obtained in the same manner as in Example 1, except that the type of inorganic particles was changed as shown in Table 2. The measurement results of the porous layer, the porous film, and the battery using the same are shown in Table 3.
[0121] (Comparative Examples 1 to 4) A porous film of the present invention was obtained in the same manner as in Example 1, except that the type, shape, and particle size of the inorganic particles were changed as shown in Table 2. The measurement results of the porous layer, the porous film, and the battery using the same are shown in Table 3.
[0122] (Comparative Examples 5 to 6) A porous film of the present invention was obtained in the same manner as in Example 1, except that the particle size and composition of the organic resin were changed to those shown in Tables 1 and 2. The measurement results of the porous layer, the porous film, and the battery using the same are shown in Table 3. In the table, HDDMA, NDDMA, DDDMA, and MMA represent 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,12-dodecyldiol di(meth)acrylate, and methyl methacrylate, respectively.
[0123] [Table 1]
[0124] [Table 2]
[0125] [Table 3]
[0126] From Tables 1, 2, and 3, all of Examples 1 to 18 have a porous substrate and a porous layer containing inorganic particles and an organic resin on at least one side of the porous substrate, the organic resin containing fluorine and having a structural unit derived from an acrylic acid ester monomer, and further, when the maximum value of the surface elastic modulus of the porous layer is α in 50 measurements of the surface elastic modulus, α is 1 GPa or more and 10 GPa or less, and the arithmetic mean height (Sa) of the porous layer in a 2200 μm square is 10 nm or more and 90 nm or less. The porous film has excellent adhesion to electrodes and heat resistance, and also has good high-rate characteristics and nail penetration resistance.
[0127] On the other hand, in Comparative Examples 1 and 2, since α is larger than 10 GPa, the arithmetic mean height (Sa) of the porous layer in a 2200 μm square is large, and the contact area with the electrode is reduced, resulting in poor dry adhesion and wet adhesion to the electrode. In Comparative Example 3, the particle size of the inorganic particles is small, the arithmetic mean height (Sa) of the porous layer in a 2200 μm square is small, and ion permeability is reduced, resulting in poor high-rate characteristics. In Comparative Example 4, the particle size of the inorganic particles is large, the arithmetic mean height (Sa) of the porous layer in a 2200 μm square is high, and the contact area with the electrode is reduced, resulting in poor dry adhesion and wet adhesion to the electrode. In Comparative Example 5, the particle size of the organic resin is large, and the organic resin is unlikely to be unevenly distributed on the surface, so sufficient adhesion to the electrode is not obtained. In Comparative Example 6, since the organic resin monomer does not contain fluorine, the organic resin particles are not unevenly distributed on the surface, so sufficient adhesion to the electrode is not obtained.
Claims
1. A porous substrate and a porous layer containing inorganic particles and an organic resin on at least one surface of the porous substrate, the organic resin contains fluorine and has a structural unit derived from an acrylic acid ester monomer, When the surface elastic modulus of the porous layer is measured 50 times, the maximum value of the surface elastic modulus is defined as α, and α is 1 GPa or more and 10 GPa or less, The porous film has an arithmetic mean height (Sa) of 10 nm or more and 90 nm or less in a 2200 μm square of the porous layer.
2. The porous film according to claim 1 , wherein a mass content of the inorganic particles contained in the porous layer is 50% by mass or more and 95% by mass or less with respect to the entire porous layer.
3. 3. The porous film according to claim 1, wherein the volume content γ of the inorganic particles and the occupancy rate δ of the inorganic particles on the surface portion of the porous layer satisfy 0<δ / γ<1 when the total volume of all components of the porous layer is 100% by volume.
4. The porous film according to claim 1 or 2, wherein the surface elastic modulus of the porous layer is measured 50 times, and the minimum value of the surface elastic modulus is defined as β, and the value of α / β is 1.5 or more and less than 10.
5. The porous film according to claim 1 or 2, wherein the organic resin comprises organic resin particles.
6. The porous film according to claim 1 or 2, wherein the inorganic particles include at least one particle selected from the group consisting of boehmite, barium sulfate, and magnesium oxide.
7. The porous film according to claim 1 or 2, wherein the inorganic particles have an average particle size of 0.3 μm or more and 1.2 μm or less.
8. The organic resin has a structural unit derived from a fluorine-containing (meth)acrylic acid ester monomer and a structural unit derived from a (meth)acrylic acid ester monomer having two or more reactive groups per molecule. The porous film according to claim 1 or 2.
9. The porous film according to claim 8, wherein the structural unit derived from a (meth)acrylic acid ester monomer having two or more reactive groups per molecule contains an alkyldiol group having six or more carbon atoms.
10. The porous film according to claim 8 , wherein the organic resin further has a structural unit derived from at least one cyclic hydrocarbon group-containing (meth)acrylic acid ester monomer.
11. The organic resin has a ratio of structural units derived from (meth)acrylic acid ester monomers having two or more reactive groups per molecule when the total monomer components of the organic resin are taken as 100% by mass. The porous film according to claim 8, wherein the ratio is 0.5% by mass or more and less than 10.0% by mass.
12. 11. The porous film according to claim 10, wherein the organic resin contains at least one cyclic hydrocarbon group-containing (meth)acrylic acid ester monomer in a proportion of 20% by mass or more and 70% by mass or less when the total monomer components of the organic resin are taken as 100% by mass.
13. 9. The porous film according to claim 8, wherein the proportion of structural units derived from fluorine-containing (meth)acrylic acid ester monomers is greater than 20% by mass and less than 60% by mass when the total monomer components of the organic resin are taken as 100% by mass.
14. A separator for a secondary battery, comprising the porous film according to claim 1 or 2.
15. A secondary battery comprising the separator for a secondary battery according to claim 14.
16. A vehicle, an unmanned transport vehicle, an electronic device, or an electricity storage device comprising the secondary battery according to claim 15.
Citation Information
Patent Citations
Driving controller for moving type incore calibrator
JP1986091597A
Separator for nonaqueous secondary battery, and nonaqueous secondary battery
JP2012221741A
Separator with heat-resistant insulating layer
JP2013080676A
Separator for secondary cell
WO2013151144A1
Separator for nonaqueous electrolyte cell, nonaqueous electrolyte cell, and method for manufacturing nonaqueous electrolyte cell
WO2016098684A1